Comparison of Uniform Theory of Diffraction Coefficients for Delay Spread and Angle Spread Estimation Using Game Engines in MIMO (2015)
In this paper, we show the results of the comparison between two different sets of heuristic uniform theory of diffraction (UTD) coefficients and its influence on the results for delay spread and angle spread. We compared our simulation results with measurements in an outdoor environment, showing the influence of the UTD coefficients in the accuracy of the results. The proposed coefficients show a better behavior than a classical set of coefficients widely used in literature.